Research on Job Stress and Nurse Performance - Sweetina Merkusi; Qurratul Aini (Universitas Muhammadiyah Yogyakarta, 2020)
In 2018-2019 there was an increase in patient visits at Kumala Siwi Kudus General Hospital, recorded to reach 4253 patients and an increase in BOR reaching 85.88%. This phenomenon resulted in an increased workload. Along with the increase in workload and the limited number of nurses providing services, it causes stress, which causes the nurse's condition to become unstable. In January 2019, a 2nd-year verification survey was carried out by KARS, which obtained recommendations to be followed up, especially reports of patient safety incidents. There was an increase in incidents from year to year, starting from 2016-2018. This study aims to determine the effect of work stress on the incidence of near injury and its impact on inpatient nurses' performance. This type of research is a quantitative study with a cross-sectional survey in this study amounted to 68 nurses in the Inpatient Installation of Kumala Siwi Kudus Hospital. This type of research is quantitative research; it is proven that stress affects nurses' perceptions of near misses and inpatient nurses' performance.